PROBLEMS AND SOLUTIONS OF TEACHING MODERN PHYSICS IN HIGHER EDUCATION - N.Z.Mamadaliyeva (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. The article analyzes the issues of what new courses should be introduced as a special subject for bachelors, masters and students of retraining and advanced training courses for teachers in the "Physics" training direction, the scope of teaching the selected subjects, what criteria should be used in their selection, its naming, in particular, the term "modern physics", its content - essence and differences from "classical" physics, theoretical analyses and solutions, as well as some current issues of teaching modern physics as a special elective subject.